UNHULLED RICE DRYING RATE IN IMPACT OF ROTARY DRYER ELEVATION ANGLE AND INLET GAS TEMPERATURE - Rosalina Rosalina; Gusni Sushanti; Puji Rahayu; Dwi Kemala Putri (AGROINTEK, 2023)
Rotary Dryer is a type of dryer that uses a rotating system to prevail the contact of wet material with hot air. LPG gas is used as a heat source assisted by a blower for air circulation in the Rotary Dryer. Using a drying chamber with a diameter of 25 cm, a length of 135 cm, a rotating speed of 7.5 rotary per second and 8 flights in it. The research method used is a completely randomized design method with variations in the angle of elevation or slope of the Rotary Dryer and the inlet gas temperature of the drying chamber with unhulled rice as raw material. The elevation angle variable used 4 levels, namely 9.16o, 11.84o, 14.47o and 16.19o, while the gas inlet temperature variable has three levels, that are 110oC, 115oC and 120oC. Measurement of moisture content using a wet basis, determining the rate of drying using the graphical integration method. The highest drying rate was obtained for changes in the slope of the Rotary Dryer at the gas inlet temperature of 115oC and a slope of 9.16o as 0.140 kg.H2O/m2.hour. However, from the linear regression equation, the most linear drying rate decrease is at the gas inlet temperature of 110oC with the equation y = -0.0054x+0.1778 with a regression coefficient value of 0.9909 almost 1. The most optimal elevation angle in decreasing water content in all temperature variations is the smallest angle, which is 9.16o with the result that the product water content comply for SNI 6128_2015 standard, which is below 14%.